Communal upheaval as resurgence of social Darwinism - Breman, Jan (2002)
There can be no two opinions about the well-entrenched nature of the Hindutva movement and its predecessors in Gujarat, strongly opposed to communal harmony and to the design of society as a melting pot of diverse and open-ended social segments. However, this explanation of the recent tragic events in the state has to be contextualised within the changing political economic of Gujarat. The comments that follow relate to Ahmedabad, the primary location of many of the horrors that have been reported. - Reproduced.
Keywords: Communalism